2018
DOI: 10.1042/bsr20180111
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces BH4 deficiency in male, but not female, SHR

Abstract: We previously published that female spontaneously hypertensive rats (SHR) have significantly greater nitric oxide (NO) bioavailability and NO synthase (NOS) enzymatic activity in the renal inner medulla (IM) compared with age-matched males, although the mechanism responsible remains unknown. Tetrahydrobiopterin (BH4) is a critical cofactor required for NO generation, and decreases in BH4 as a result of increases in oxidative stress have been implicated in the pathogenesis of hypertension. As male SHR are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
8
1
1
Order By: Relevance
“…Indeed, treatment with the NADPH oxidase inhibitor apocynin attenuated Ang II-induced increases in BP only in male SHR, thereby abolishing the sex difference in the Ang II-BP response [ 11 ]. However, treatment with apocynin alone for 1 week had no effect on BP in male or female SHR and treatment with the SOD mimetic tempol for 2 weeks does not alter baseline BP in male or female SHR [ 72 ]. Tempol treatment with for 6 weeks reduced BP only in male SHR [ 13 ] and terminal BP measured via femoral catheter indicated a decrease in BP in only male SHR following 7 days treatment with apocynin [ 76 ].…”
Section: Mechanisms Mediating Sex Differences In Bp In Shrmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, treatment with the NADPH oxidase inhibitor apocynin attenuated Ang II-induced increases in BP only in male SHR, thereby abolishing the sex difference in the Ang II-BP response [ 11 ]. However, treatment with apocynin alone for 1 week had no effect on BP in male or female SHR and treatment with the SOD mimetic tempol for 2 weeks does not alter baseline BP in male or female SHR [ 72 ]. Tempol treatment with for 6 weeks reduced BP only in male SHR [ 13 ] and terminal BP measured via femoral catheter indicated a decrease in BP in only male SHR following 7 days treatment with apocynin [ 76 ].…”
Section: Mechanisms Mediating Sex Differences In Bp In Shrmentioning
confidence: 99%
“…NO is produced by the enzyme NOS, and there are three NOS isoforms: NOS1 (neuronal NOS, nNOS), NOS2 (inducible NOS, iNOS) and NOS 3 (endothelial NOS, eNOS) [ 85 ]. Excess superoxide preferentially binds NO resulting in decrease in NO bioavailability and the production of peroxynitrite [ 21 , 70 , 72 ]. Decreases in NO bioavailability contribute to endothelial dysfunction and the progression of cardiovascular disease [ 70 ].…”
Section: Mechanisms Mediating Sex Differences In Bp In Shrmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported sex-specific differences in renal responses to environmentally-induced oxidative stress in mice. These differences may be a consequence of gender-related differences in the activities of oxidative stress response enzymes [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneously Hypertensive Rats (SHR) and Wistar-Kyoto (WKY) male rats (8-10 weeks old) were used due to the greater levels of oxidative stress of male SHR compared with female SHR. In this regards, Gillis et al demonstrated that higher oxidative stress in male SHR conduces to a deficiency of Tetrahydrobiopterin (BH 4 ), a critical cofactor required for NO generation, resulting in diminished renal NOS activity [23]. Indirect systolic blood pressure was measured by the tail cuff method prior to perform the experiments, using a pulse sensor photoelectric CCP model in a Grass polygraph model 7 equipped with a 7P8 pre-amplified (Grass Medical Instruments).…”
Section: Animalsmentioning
confidence: 99%